Electron heating in the exhaust of magnetic reconnection with negligible guide field. Issue 3 (15th March 2016) - Wang, Shan; Chen, Li‐Jen; Bessho, Naoki; Kistler, Lynn M.; Shuster, Jason R.; Guo, Ruilong
Abstract: Electron heating in the magnetic reconnection exhaust is investigated with particle‐in‐cell simulations, space observations, and theoretical analysis. Spatial variations of the electron temperature ( Te ) and associated velocity distribution functions (VDFs) are examined and understood in terms of particle energization and randomization processes that vary with exhaust locations. Inside the electron diffusion region (EDR), the electron temperature parallel to the magnetic field ( T e ∥ ) exhibits a local minimum and the perpendicular temperature ( T e ⊥ ) shows a maximum at the current sheet midplane. In the intermediate exhaust downstream from the EDR and far from the magnetic field pileup region, T e ⊥ / T e ∥ is close to unity and Te is approximately uniform, but the VDFs are structured: close to the midplane, VDFs are quasi‐isotropic, whereas farther away from the midplane, VDFs exhibit field‐aligned beams directed toward the midplane. In the far exhaust, Te generally increases toward the midplane and the pileup region, and the corresponding VDFs show counter‐streaming beams. A distinct population with low v ∥ and high v ⊥ is prominent in the VDFs around the midplane. Test particle results show that the magnetic curvature near the midplane produces pitch angle scattering to generate quasi‐isotropic distributions in the intermediate exhaust. In the far exhaust, electrons with initial high v ∥ ( v ⊥ ) are accelerated mainly through curvature (gradient‐B) drift opposite to the electric field, without significant pitch angle scattering. The VDF structures predicted by simulations are observed in magnetotail reconnection measurements, indicating that the energization mechanisms captured in the reported simulations are applicable to magnetotail reconnection with negligible guide field. Key Points: Exhaust e‐heating results from acceleration, gyrotropization, pitch angle scattering, and mixing Magnetotail exhaust electron distributions confirm our results from theory and simulation Pitch angle scattering is elucidated with theory and test particles to explain isotropization